PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT SEMEN PADANG DENGAN KEPUASAN KERJA SEBAGAI MEDIASI - Febby Arief Zeindra; Hendra Lukito (Departemen Manajemen, 2020)
This study discusses the analysis of the Influence of Transformational Leadership Styles and Organizational Culture on Employee Performance at the Head Office of PT Semen Padang with Job Satisfaction as Mediation, which was carried out using descriptive analysis. This analysis is to strengthen the argumentation and logic in answering and implementing the assumptions that will be described in quantitative analysis. This research was conducted based on data collected from a list of questions (questionnaires) that have been submitted to and have been filled out by 129 employees. Then this data is analyzed statistically using SmartPLS software. The results of the research analysis showed that there was a positive and significant influence between transformational leadership and organizational culture on employee satisfaction, then transformational leadership and organizational culture on employee performance.